MOFs‐Derived Flower‐Like Hierarchically Porous Zn‐Mn‐Se/C Composite for Extraordinary Rate Performance and Durable Anode of Sodium‐Ion and Potassium‐Ion Batteries. Issue 34 (31st July 2022) - Zhou, Peng; Zhang, Mingyu; Wang, Liping; Huang, Qizhong; Su, Zhean; Xu, Ping; Zou, Renhao; Wang, Xiaodong; Zeng, Cen; Ba, Kaixun
Abstract: The slow kinetics and poor structural stability prevent transition metal selenides from being widely used in sodium‐ion batteries (SIBs) and potassium‐ion batteries (PIBs). Herein, the "flower‐like" porous carbon anchored by Zn‐Mn binary selenides (ZMS@FC) composites are fabricated by selenizing the modified hierarchically metal‐organic frameworks. The 2D conductive hierarchically flakes' abundant pore structure and multiple active sites shorten the ion diffusion length and promote conductivity, while the synergistic effect of the binary metals and intrinsic large pseudocapacitive contribution effectively improve capacity and rate performance. ZMS@FC composites exhibit impressive rate capability of 294.4 mA h g –1 at 10 A g –1 and excellent cyclic stability with 369.6 mA h g –1 specific capacity retention at 2 A g –1 after 1000 cycling in SIBs. It is noted that 156.9 mA h g –1 can be retained at 5 A g –1 and 227.0 mA h g –1 is remained after 500 cycles at 2 A g –1 in PIBs. The ex situ X‐ray diffraction patterns and transmission electron microscopy pictures are used to confirm the conversion reaction processes of the Zn‐Mn‐Se. Designing high‐performance energy storage materials may benefit greatly from the universal synthesis technology of bimetallic sulfide anodes for enhanced SIBs and PIBs. Abstract : Flower‐like Zn‐Mn‐Se carbon nanoflakes (ZMS@FC) with excellent Na + /K + storage performance are synthesized via selenizing the modified hierarchically metal‐organic frameworks. The ZMS@FC display excellent reversibility and high Na + /K + diffusion kinetics.